2021
DOI: 10.1186/s12940-021-00786-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term personal air pollution exposure and risk for acute exacerbation of idiopathic pulmonary fibrosis

Abstract: Background Urban air pollution is involved in the progress of idiopathic pulmonary fibrosis (IPF). Its potential role on the devastating event of Acute Exacerbation of IPF (AE-IPF) needs to be clarified. This study examined the association between long-term personal air pollution exposure and AE- IPF risk taking into consideration inflammatory mediators and telomere length (TL). Methods All consecutive IPF-patients referred to our Hospital from Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…Regarding to hospitalizations due to respiratory deterioration we observed that increases in NO 2 , O 3 , and NO x were significantly associated with the increase in the number of hospitalizations for this cause in patients with IPF with relatively long periods of exposure compared to other studies (5,6,8,29). We have found no research that examines the association between pollution and the probability of hospitalization due to respiratory causes in patients with IPF.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Regarding to hospitalizations due to respiratory deterioration we observed that increases in NO 2 , O 3 , and NO x were significantly associated with the increase in the number of hospitalizations for this cause in patients with IPF with relatively long periods of exposure compared to other studies (5,6,8,29). We have found no research that examines the association between pollution and the probability of hospitalization due to respiratory causes in patients with IPF.…”
Section: Discussioncontrasting
confidence: 65%
“…. ) and some studies recently suggested an association between air pollution and clinical course or mortality of IPF (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant cause of death in patients with IPF is acute exacerbation of idiopathic pulmonary fibrosis that accounts for 40% mortality (18)(19)(20). Exposure to fine particles and air pollution were observed as risk factors for acute exacerbation of IPF (21)(22)(23).…”
Section: Accepted Manuscript / Final Versionmentioning
confidence: 99%
“…Pneumoconiosis patients suffer from a significantly increased risk of pulmonary functions 20,21 . Recent epidemiologic studies in humans have indicated that pulmonary fibrosis is closely correlated with PMs 21,22 .…”
Section: Pms and Pulmonary Fibrosismentioning
confidence: 99%